Advances in the Evaluation of Gastrointestinal Absorption Considering the Mucus Layer - Kaori Miyazaki; Akira Sasaki; Hiroshi Mizuuchi (MDPI AG, 2023)
Because of the increasing sophistication of formulation technology and the increasing polymerization of compounds directed toward undruggable drug targets, the influence of the mucus layer on gastrointestinal drug absorption has received renewed attention. Therefore, understanding the complex structure of the mucus layer containing highly glycosylated glycoprotein mucins, lipids bound to the mucins, and water held by glycans interacting with each other is critical. Recent advances in cell culture and engineering techniques have led to the development of evaluation systems that closely mimic the ecological environment and have been applied to the evaluation of gastrointestinal drug absorption while considering the mucus layer. This review provides a better understanding of the mucus layer components and the gastrointestinal tract's biological defense barrier, selects an assessment system for drug absorption in the mucus layer based on evaluation objectives, and discusses the overview and features of each assessment system.